Optimalisasi Pendaftaran Rawat Jalan untuk Peningkatan Kualitas Pelayanan Publik di Rumah Sakit Goenawan Partowidigdo - Pratama, Tirta; Sila Wiweka, Ida Bagus; Saefulmilah, Henik (Universitas Hang Tuah Pekanbaru, 2025)
Introduction: Service waiting time is a key indicator for measuring hospital quality. However, data indicate that outpatient waiting times at several hospitals exceed the standard duration, and Goenawan Partowidigdo Hospital faces similar issues, with long queues and prolonged outpatient registration wait times. Registration via the online application was extremely low, ranging from 0.21% to 3.10% (May–July 2024 data), and the service waiting time consistently exceeded the target of >60 minutes, sometimes reaching 2 hours and 22 minutes. Objective: This study aims to optimize the outpatient registration system at Goenawan Partowidigdo Hospital through an integrated digitalization approach to reduce waiting times, relieve queue congestion, and ultimately improve the patient experience. Methods: This study used a qualitative case study design conducted from September to November 2024. Primary data were obtained through in-depth interviews with 11 key informants (4 management staff, 4 registration staff, and 3 patients) using purposive sampling. Qualitative analysis, including a fishbone diagram, was conducted to identify problems. Data on online registration utilization and waiting times were analyzed descriptively to compare the periods before and after the intervention. Results: Online registration utilization increased significantly in the post-intervention period to 86.19% in June and 87.96% in July 2025. Consequently, the waiting time decreased to approximately 1 hour and 16 minutes in June and 1 hour and 08 minutes in July 2025. Conclusion: The optimization of outpatient registration at Goenawan Partowidigdo Hospital, achieved through a holistic approach that integrated digitalization and intensive education, successfully relieved outpatient queue congestion and reduced service waiting times.